Gender Inequality and Mental Health Consequences in Kim Ji-young, Born 1982: A Critical Discourse Analysis - Soontaree Larprungrueng, Soontaree; Sinaroj, Natthawan (ARU Research Journal Humanities and Social Sciences, 2026)
This article aimed to: 1) examine the forms of gender inequality represented through the protagonist’s experiences across four major social contexts—family, education, the workplace, and public spaces; 2) investigate the cumulative effects of gender discrimination on the protagonist’s mental health through the mechanisms of chronic stress and allostatic load; and 3) analyse the discursive construction of gender inequality in the novel through feminist and gender-theoretical perspectives. The study employed a qualitative research design integrating content analysis with Norman Fairclough’s approach to Critical Discourse Analysis. The analysis was informed by interdisciplinary theoretical concepts, including patriarchy, gender performativity, emotional labour, mental load, intersectionality, and chronic stress. The primary texts comprised the original Korean edition of Kim Ji-young, Born 1982 and its Thai translation. The findings revealed that the novel represents gender inequality as a pervasive structural condition embedded in multiple spheres of life and perpetuated through language and everyday social practices. These conditions contribute to the long-term accumulation of stress, ultimately leading to the protagonist’s mental health crisis. Her psychological symptoms are not represented as an individual-level pathology but as consequences of gendered power structures that operate continuously through discourse and everyday practices. The findings illuminate the interrelationship among language, power, and mental health in literary representation and contribute to the development of an interdisciplinary framework connecting literary studies, gender studies, and mental health studies in Asian contexts. However, the findings concern representations within a literary text and should not be interpreted as empirical conclusions about society as a whole.